Composite solid electrolyte based on sulfide-polymer and preparation method thereof

By introducing partially crystallized sulfide networks and high-valent metal ions into the sulfide-polymer composite solid electrolyte, combining the cladding of metal chloride and lithium fluoride and the coating of polyaniline, the problems of poor phase separation and interface compatibility are solved, and the conductive and mechanical properties of the material are significantly improved.

CN119852504AActive Publication Date: 2025-04-18YANCHENG JINHUI HIGH-TECH MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510154615.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-18
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

The existing sulfide-polymer composite solid electrolytes have phase separation phenomena and poor interfacial compatibility, which affects their ionic conductivity and mechanical properties, resulting in a decrease in battery efficiency.

Method used

A partially crystallized sulfide network is generated by mechanochemical reactions of lithium sulfide and phosphorus pentasulfide, and doped with high-valent metal ions, optimizing the lattice structure to reduce the energy barrier for the transfer of lithium ion. At the same time, a cladding layer of metal chloride and lithium fluoride is used to isolate moisture and oxygen in the environment, and the interface impedance is reduced by the coating of polyaniline.

Benefits of technology

It significantly improves the conductivity, mechanical properties and cyclic stability of the material, forms a dual continuous ion conductive network, and optimizes the interface impedance and ion transmission performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852504A_ABST
    Figure CN119852504A_ABST
Patent Text Reader

Abstract

The invention provides a sulfide-polymer composite solid electrolyte and a preparation method thereof, and belongs to the field of batteries. Lithium sulfide and phosphorus pentasulfide react to generate a partially crystallized sulfide network, and high-valence metal ions are doped to optimize a lattice structure, so that the conductivity and the chemical stability are enhanced; the crystal phase provides an efficient ion migration channel, and the amorphous region reduces the grain boundary effect and improves the conduction uniformity; a metal chloride and lithium fluoride coating layer is used for isolating moisture and oxygen, and polyaniline coating is used for reducing interface impedance and enhancing cycling stability. The crystallinity is reduced and an amorphous region is increased through sulfonated polyetheretherketone, so that a low-impedance path is provided for lithium ions; a polyethylene glycol chain segment improves the flexibility and the ion migration ability, and a three-dimensional network structure is formed through crosslinking to enhance the mechanical strength and the interface stability. And the inorganic phase and the polymer have a synergistic effect to construct a bicontinuous ionic conductive network to improve the comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a sulfide-polymer composite solid electrolyte and a preparation method thereof. Background Art

[0002] In recent years, solid-state electrolytes have gradually become a hot topic in solid-state battery research due to their superior safety and high energy density. Compared with traditional liquid batteries, solid-state batteries have higher safety and can effectively reduce the risk of leakage, combustion and explosion; at the same time, the high energy density of solid-state electrolytes makes the battery more advantageous in volume and weight, and is suitable for application scenarios with high energy requirements, such as electric vehicles and energy storage systems.

[0003] Among the many types of solid electrolytes, sulfide-polymer composite solid electrolytes have attracted much attention due to their unique material properties. This type of composite material combines the advantages of sulfide electrolytes and polymer electrolytes, making them excellent in ionic conductivity and mechanical strength. Sulfide electrolytes, such as lithium sulfide and phosphorus pentasulfide, exhibit extremely high ionic conductivity, which can usually reach the level of liquid electrolytes. However, these sulfide materials generally have the problems of large brittleness and easy deliquesce, which limits their wide application and durability in practical applications. On the other hand, polymer electrolytes are known for their good flexibility and processability, and can be well adapted in batteries of different shapes and sizes, but their ionic conductivity is relatively low and usually cannot meet the needs of high-power applications. By combining these two materials to form a sulfide-polymer composite solid electrolyte, their respective shortcomings can be effectively overcome and the overall performance can be improved. This composite material can not only improve ionic conductivity, but also enhance mechanical strength, thereby improving the stability and service life of the electrolyte.

[0004] Despite this, existing sulfide-polymer composite solid electrolytes still have some shortcomings. First, traditional composite methods often lead to phase separation, which affects the overall ionic conductivity and mechanical properties of the electrolyte, resulting in a decrease in battery efficiency. Secondly, the poor interfacial compatibility between sulfides and polymers may cause an increase in interfacial impedance, which limits the transport of ions in the electrolyte and further reduces the overall efficiency of the battery. Therefore, research and improvement on these deficiencies is an important topic in the current field of solid-state batteries and is also the key to promoting the technology towards commercialization. Summary of the invention

[0005] In view of the above problems, the purpose of the present invention is to provide a sulfide-polymer composite solid electrolyte and a preparation method thereof. In the present invention, a partially crystallized sulfide network is generated by a mechanochemical reaction of lithium sulfide and phosphorus pentasulfide, and the lattice structure is optimized by doping high-valent metal ions, thereby reducing the energy barrier for lithium ion migration, and enhancing the conductivity and chemical stability. The crystalline phase structure provides an efficient lithium ion migration channel, and the amorphous region reduces the grain boundary effect and improves the uniformity of ion conductivity; at the same time, the coating layer of metal chloride and lithium fluoride is used to isolate the moisture and oxygen in the environment, significantly improving the environmental stability and durability of the inorganic phase, and the coating of polyaniline further improves the structural stability of the material during the cycle by reducing the interface impedance and enhancing the flexibility. Sulfonated polyetheretherketone improves lithium affinity by introducing sulfonic acid groups, reduces crystallinity and increases amorphous regions, providing a low impedance path for lithium ion transmission; the polyethylene glycol segment enhances flexibility and ion migration ability, and forms a three-dimensional network structure through cross-linking, further improving mechanical strength and interface stability. Finally, the inorganic phase forms a dual continuous ion conductive network through the high conductivity main channel and the flexible filling effect of the polymer, and the interface optimization of the coating layer and the conductive polymer is combined to effectively reduce the interface impedance and enhance the ion transport performance. The synergistic effect of the inorganic phase and the polymer significantly improves the conductivity, mechanical properties and cycle stability of the material.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a sulfide-polymer composite solid electrolyte, the method for preparing a sulfide-polymer composite solid electrolyte comprising:

[0008] S1: The mixed powder obtained by ball milling the sulfide and the inorganic salt is heat treated in an argon atmosphere to obtain an inorganic core body;

[0009] S2: melting lithium sulfide and phosphorus pentasulfide, cooling them, and then heat treating them to obtain an inorganic phase precursor; mixing the inorganic phase precursor with the inorganic core body and heat treating them to obtain a composite inorganic phase;

[0010] S3: dissolving indium trichloride and lithium chloride in anhydrous ethanol, adding acetic acid and then refluxing to obtain a precursor solution, reacting the composite inorganic phase with the precursor solution, and subjecting the composite inorganic phase to a heat treatment to obtain a first coating inorganic phase;

[0011] S4: dispersing ammonium fluoride and lithium acetate in anhydrous ethanol to obtain a second precursor solution, reacting the first coating inorganic phase with the second precursor solution, and subjecting the reaction to heat treatment to obtain a double-layer coating product; compounding polyaniline with the double-layer coating product to obtain a conductive layer coating inorganic phase;

[0012] S5: dispersing polyetheretherketone in concentrated sulfuric acid to obtain sulfonated polyetheretherketone, and reacting the sulfonated polyetheretherketone with methoxy polyethylene glycol to obtain a modified polymer;

[0013] S6: Dispersing the modified polymer in N,N-dimethylformamide, adding a conductive layer-coated inorganic phase, a cross-linking agent, an initiator and a lithium salt, and mixing to obtain a uniform mixed solution, and casting the film to obtain a composite solid electrolyte by cross-linking.

[0014] Specifically,

[0015] S1: mixing sulfide and inorganic salt and ball-milling to obtain mixed powder; heat-treating the mixed powder under argon atmosphere to obtain an inorganic core body;

[0016] S2: Lithium sulfide and phosphorus pentasulfide are melted in an argon atmosphere and then cooled to obtain a glass precursor, which is heat-treated to obtain an inorganic phase precursor; the inorganic phase precursor and the inorganic core body are mixed, ball-milled, and then heat-treated to obtain a composite inorganic phase;

[0017] S3: dissolving indium trichloride and lithium chloride in anhydrous ethanol, adding acetic acid to adjust the pH, and refluxing to obtain a precursor solution; dispersing the composite inorganic phase in anhydrous ethanol to obtain a composite inorganic phase dispersion, dripping the precursor solution at a constant temperature and stirring, centrifuging, washing, and heat-treating in an argon atmosphere to obtain a first coating inorganic phase;

[0018] S4: Disperse ammonium fluoride and lithium acetate in anhydrous ethanol to obtain a second precursor solution; disperse the first coating inorganic phase in anhydrous ethanol to obtain dispersion A, add the second precursor solution dropwise and stir, centrifuge, wash, and heat-treat in an argon atmosphere to obtain a double-layer coating inorganic phase; disperse polyaniline in N-methylpyrrolidone to obtain dispersion B, add the double-layer coating inorganic phase to dispersion B, stir at room temperature, centrifuge, wash, and dry to obtain a conductive layer coating inorganic phase.

[0019] S5: Disperse polyetheretherketone in concentrated sulfuric acid, stir, slowly pour the reaction solution into ice water, filter, wash, and vacuum dry to obtain sulfonated polyetheretherketone; disperse it in N,N-dimethylformamide, add sodium hydroxide solution to adjust the pH, dropwise add N,N-dimethylformamide solution of methoxypolyethylene glycol, react to obtain a reaction solution, pour the reaction solution into deionized water, filter, wash, and dry to obtain a modified polymer;

[0020] S6: Disperse the modified polymer in N,N-dimethylformamide, add polyethylene glycol dimethacrylate and azobisisobutyronitrile, and perform ultrasonic dispersion to obtain a polymer solution; disperse the conductive layer coated inorganic phase in N,N-dimethylformamide, wherein the mass ratio of the modified polymer to the conductive layer coated inorganic phase is (20-40):(60-80), add the polymer solution, and then add lithium salt and disperse evenly to obtain a uniform mixed solution, cast the film, pre-dry, heat-induced cross-link, and vacuum dry to obtain a sulfide-polymer composite solid electrolyte.

[0021] As a preferred technical solution of the present invention, in step S1, the molar ratio of lithium sulfide to phosphorus pentasulfide is 7-8:3, for example, it can be 7.0:3, 7.1:3, 7.2:3, 7.3:3, 7.4:3, 7.5:3, 7.6:3, 7.7:3, 7.8:3, 7.9:3 or 8.0:3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] In some optional embodiments, the molar ratio of the sulfide to the inorganic salt is 1:0.05-0.15, for example, it can be 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.10, 1:0.11, 1:0.12, 1:0.13, 1:0.14 or 1:0.15, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] In some optional embodiments, the heating rate of the mixed powder heat treatment is 5-10℃ / min, for example, it can be 5.0℃ / min, 5.5℃ / min, 6.0℃ / min, 6.5℃ / min, 7.0℃ / min, 7.5℃ / min, 8.0℃ / min, 8.5℃ / min, 9.0℃ / min, 9.5℃ / min or 10.0℃ / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In some optional embodiments, the temperature of the mixed powder heat treatment is 300-400°C, for example, it can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] In some optional embodiments, the mixed powder heat treatment time is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] As a preferred technical solution of the present invention, in step S2, the molar ratio of lithium sulfide to phosphorus pentasulfide is 2-2.5:1, for example, it can be 2.00:1, 2.05:1, 2.10:1, 2.15:1, 2.20:1, 2.25:1, 2.30:1, 2.35:1, 2.40:1, 2.45:1 or 2.50:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In some optional embodiments, the melting temperature is 550-600°C, for example, it can be 550°C, 555°C, 560°C, 565°C, 570°C, 575°C, 580°C, 585°C, 590°C, 595°C or 600°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In some optional embodiments, the melting time is 10-20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In some optional embodiments, the temperature of the heat treatment of the glassy precursor is 250-300°C, for example, it can be 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C or 300°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In some optional embodiments, the heat treatment time of the glassy precursor is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] In some optional embodiments, the mass ratio of the inorganic phase precursor to the inorganic core body is 8-9:1, for example, it can be 8.0:1, 8.1:1, 8.2:1, 8.3:1, 8.4:1, 8.5:1, 8.6:1, 8.7:1, 8.8:1, 8.9:1 or 9.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In some optional embodiments, the temperature of heat treatment after mixed ball milling of the inorganic phase precursor and the inorganic core body is 300-400°C, for example, it can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In some optional embodiments, the heat treatment time after the inorganic phase precursor and the inorganic core body are mixed and ball-milled is 1-2h, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] As a preferred technical solution of the present invention, in step S3, the molar ratio of indium trichloride to lithium chloride is 1:2-3, for example, it can be 1:2.0, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9 or 1:3.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In some optional embodiments, the concentration of the indium trichloride in anhydrous ethanol is 0.1-0.3M, for example, it can be 0.10M, 0.11M, 0.12M, 0.13M, 0.14M, 0.15M, 0.16M, 0.17M, 0.18M, ​​0.19M or 0.20M, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In some optional embodiments, acetic acid is added to adjust the pH to 4-5, for example, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9 or 5.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] In some optional embodiments, the reflux temperature is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] In some optional embodiments, the reflux time is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] In some optional embodiments, the mass fraction of the composite inorganic phase in anhydrous ethanol is 5-6wt.%, for example, it can be 5.0wt.%, 5.1wt.%, 5.2wt.%, 5.3wt.%, 5.4wt.%, 5.5wt.%, 5.6wt.%, 5.7wt.%, 5.8wt.%, 5.9wt.% or 6.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In some optional embodiments, the mass ratio of the composite inorganic phase to the precursor solution is 1:8-12, for example, it can be 1:8.0, 1:8.4, 1:8.8, 1:9.2, 1:9.6, 1:10.0, 1:10.4, 1:10.8, 1:11.2, 1:11.6 or 1:12.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] In some optional embodiments, the composite inorganic phase dispersion is dripped into the precursor solution at a constant temperature of 60-70°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] In some optional embodiments, the composite inorganic phase dispersion is dripped into the precursor solution at a constant temperature and stirred for 4-5 hours, for example, 4.0 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In some optional embodiments, the temperature of the heat treatment is 250-300°C, for example, it can be 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C or 300°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] In some optional embodiments, the heat treatment time is 1-2h, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] As a preferred technical solution of the present invention, in step S4, the concentration of ammonium fluoride dispersed in anhydrous ethanol is 0.2-0.3 mol / L, for example, it can be 0.20 mol / L, 0.21 mol / L, 0.22 mol / L, 0.23 mol / L, 0.24 mol / L, 0.25 mol / L, 0.26 mol / L, 0.27 mol / L, 0.28 mol / L, 0.29 mol / L or 0.30 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] In some optional embodiments, the concentration of lithium acetate dispersed in anhydrous ethanol is 0.2-0.3 mol / L, for example, it can be 0.20 mol / L, 0.21 mol / L, 0.22 mol / L, 0.23 mol / L, 0.24 mol / L, 0.25 mol / L, 0.26 mol / L, 0.27 mol / L, 0.28 mol / L, 0.29 mol / L or 0.30 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In some optional embodiments, the mass fraction of the first coated inorganic phase in anhydrous ethanol is 3-4wt.%, for example, it can be 3.0wt.%, 3.1wt.%, 3.2wt.%, 3.3wt.%, 3.4wt.%, 3.5wt.%, 3.6wt.%, 3.7wt.%, 3.8wt.%, 3.9wt.% or 4.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] In some optional embodiments, the mass ratio of the first coating inorganic phase to the second precursor solution is 1:6-10, for example, it can be 1:6.0, 1:6.4, 1:6.8, 1:7.2, 1:7.6, 1:8.0, 1:8.4, 1:8.8, 1:9.2, 1:9.6 or 1:10.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] In some optional embodiments, the stirring temperature of the dispersion A after adding the second precursor solution is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In some optional embodiments, the stirring time after the dispersion A is added with the second precursor solution is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In some optional embodiments, the heat treatment temperature is 150-160°C, for example, it can be 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] In some optional embodiments, the heat treatment time is 1-2h, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] In some optional embodiments, the mass fraction of the polyaniline dispersed in N-methylpyrrolidone is 2-3wt.%, for example, it can be 2.0wt.%, 2.1wt.%, 2.2wt.%, 2.3wt.%, 2.4wt.%, 2.5wt.%, 2.6wt.%, 2.7wt.%, 2.8wt.%, 2.9wt.% or 3.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In some optional embodiments, the mass ratio of the double-layer coated inorganic phase to polyaniline is 95:5-98:2, for example, it can be 95:5, 95.5:4.5, 96:4, 96.5:3.5, 97:3, 97.5:2.5 or 98:2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In some optional embodiments, the double-layer coated inorganic phase is added to dispersion B and stirred at room temperature for 4-5 hours, for example, 4.0 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] As a preferred technical solution of the present invention, in step S5, the mass fraction of the polyetheretherketone in concentrated sulfuric acid is 4-5wt.%, for example, it can be 4.0wt.%, 4.1wt.%, 4.2wt.%, 4.3wt.%, 4.4wt.%, 4.5wt.%, 4.6wt.%, 4.7wt.%, 4.8wt.%, 4.9wt.% or 5.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] In some optional embodiments, the stirring temperature is 40-50°C, for example, it can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] In some optional embodiments, the stirring time is 10-12h, for example, it can be 10.0h, 10.2h, 10.4h, 10.6h, 10.8h, 11.0h, 11.2h, 11.4h, 11.6h, 11.8h or 12.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] In some optional embodiments, the mass fraction of the sulfonated polyetheretherketone in N,N-dimethylformamide is 10-15wt.%, for example, it can be 10.0wt.%, 10.5wt.%, 11.0wt.%, 11.5wt.%, 12.0wt.%, 12.5wt.%, 13.0wt.%, 13.5wt.%, 14.0wt.%, 14.5wt.% or 15.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] In some optional embodiments, the concentration of the sodium hydroxide solution is 1-2M, for example, it can be 1.0M, 1.1M, 1.2M, 1.3M, 1.4M, 1.5M, 1.6M, 1.7M, 1.8M, 1.9M or 2.0M, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] In some optional embodiments, the pH is adjusted to 8-9 using sodium hydroxide solution, for example, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9 or 9.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] In some optional embodiments, the mass fraction of the N,N-dimethylformamide solution of methoxypolyethylene glycol is 15-20wt.%, for example, it can be 15.0wt.%, 15.5wt.%, 16.0wt.%, 16.5wt.%, 17.0wt.%, 17.5wt.%, 18.0wt.%, 18.5wt.%, 19.0wt.%, 19.5wt.% or 20.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] In some optional embodiments, the mass ratio of the methoxy polyethylene glycol to the sulfonated polyetheretherketone is 1-2:1, for example, it can be 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] In some optional embodiments, the reaction temperature is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] In some optional embodiments, the reaction time is 20-24h, for example, it can be 20.0h, 20.5h, 21.0h, 21.5h, 22.0h, 22.5h, 23.0h, 23.5h or 24.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] As a preferred technical solution of the present invention, in step S6, the mass fraction of the modified polymer in N,N-dimethylformamide is 10-15wt.%, for example, it can be 10.0wt.%, 10.5wt.%, 11.0wt.%, 11.5wt.%, 12.0wt.%, 12.5wt.%, 13.0wt.%, 13.5wt.%, 14.0wt.%, 14.5wt.% or 15.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] In some optional embodiments, the mass ratio of the crosslinking agent to the modified polymer is 0.2-0.3:1, for example, it can be 0.20:1, 0.21:1, 0.22:1, 0.23:1, 0.24:1, 0.25:1, 0.26:1, 0.27:1, 0.28:1, 0.29:1 or 0.30:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] In some optional embodiments, the amount of the initiator is 0.05-0.15% of the mass of the cross-linking agent, for example, it can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14% or 0.15%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] In some optional embodiments, the mass fraction of the conductive layer coated inorganic phase in N,N-dimethylformamide is 15-20wt.%, for example, it can be 15.0wt.%, 15.5wt.%, 16.0wt.%, 16.5wt.%, 17.0wt.%, 17.5wt.%, 18.0wt.%, 18.5wt.%, 19.0wt.%, 19.5wt.% or 20.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] In some optional embodiments, the concentration of the lithium salt in the uniform mixed solution is 0.1-0.3M, for example, it can be 0.10M, 0.12M, 0.14M, 0.16M, 0.18M, ​​0.20M, 0.22M, 0.24M, 0.26M, 0.28M or 0.30M, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] In some optional embodiments, the pre-drying temperature after the cast film is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0072] In some optional embodiments, the pre-drying time after the cast film is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0073] In some optional embodiments, the temperature of heat-induced crosslinking is 120-130°C, for example, it can be 120°C, 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C or 130°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0074] In some optional embodiments, the time for heat-induced crosslinking is 2-3 h, for example, 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h or 3.0 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0075] In a second aspect, the present invention provides a sulfide-polymer composite solid electrolyte.

[0076] In the present invention, lithium sulfide and phosphorus pentasulfide are used as raw materials, and a sulfide precursor is formed through the high-energy mechanical action of ball milling. During the ball milling process, high-energy impact and shear force promote a mechanochemical reaction between lithium sulfide and phosphorus pentasulfide to generate a sulfide network structure. These sulfide materials exhibit excellent lithium ion conductivity due to their unique structural characteristics, and their high lithium ion diffusion coefficient and low ion migration activation energy make them an ideal component of solid electrolytes. In this process, the formation of the sulfide network provides a preliminary framework for the efficient migration of lithium ions.

[0077] At the same time, inorganic salts (lanthanum trichloride, gallium chloride, aluminum trichloride) partially enter the sulfide network through ion exchange or physical doping during the ball milling process. 3 +、Ga 3High-valent metal ions such as Al+ and Al3+ interact with phosphorus or sulfur sites in sulfides to achieve local cation substitution, thereby introducing doping into the sulfide network. On the one hand, these doped ions break the original symmetry and form structural defects by changing the lattice parameters of the sulfide; on the other hand, these defects can serve as "energy valleys" for lithium ion migration, reducing the energy barriers in the lithium ion diffusion path, thereby effectively reducing the activation energy of lithium ion diffusion. In addition, the introduction of doped ions will also change the local electric field distribution of the sulfide, providing additional electric field driving force, which will help the rapid diffusion of lithium ions in the network.

[0078] More importantly, doping with metal ions also has a "passivation" effect on the surface of sulfide materials. Sulfide materials are usually highly sensitive to moisture and oxygen in the air, and are prone to hydrolysis or oxidation reactions, resulting in decreased conductivity. However, doping ions can stabilize the surface chemical environment and reduce the activity of surface chemical reactions by interacting with surface sulfide groups, thereby significantly improving the environmental stability and long-term storage performance of sulfide precursors.

[0079] On this basis, after the heat treatment process, the solid-phase reaction between the inorganic salt and the sulfide is further deepened, the distribution of the doped ions is more uniform, and the doping effect is significantly improved. This uniformly distributed doping improves the overall electrochemical properties of the sulfide network, especially the uniformity of lithium ion migration. At the same time, heat treatment may also induce the transformation of some sulfides from amorphous to subcrystalline or microcrystalline. During this transformation process, the local order inside the sulfide is enhanced, forming a continuous lithium ion migration channel, which significantly optimizes the ion conductivity of the material. In addition, the formation of subcrystalline or microcrystalline states also helps to enhance the mechanical strength of the material and avoid the mechanical fragility that may exist in completely amorphous materials. Therefore, heat treatment not only improves the chemical uniformity of doping, but also further optimizes the electrical conductivity and mechanical properties of sulfides through structural regulation, so that the inorganic core has excellent ion conductivity and structural stability.

[0080] Under high temperature conditions, lithium sulfide and phosphorus pentasulfide are fully mixed and react chemically through a melt reaction to generate a glassy sulfide precursor with high purity. In this process, the high temperature provides sufficient thermal energy to quickly break the chemical bonds between lithium sulfide and phosphorus pentasulfide and reform the sulfide network structure. The products generated by these reactions have a uniform chemical composition, but due to rapid cooling, the material does not undergo a sufficient crystallization process, and finally forms a completely amorphous glassy sulfide. Glassy sulfides exhibit irregular ion distribution, lack long-range ordered crystal arrangement, and retain a large number of amorphous regions. These amorphous regions provide great advantages for the migration of lithium ions. Lithium ions can achieve rapid migration in the amorphous structure by dynamically coordinating and dissociating with polar groups in the amorphous network. The high degree of freedom of the amorphous structure gives glassy sulfides a low ion diffusion activation energy, which enables them to exhibit excellent performance in ionic conductivity.

[0081] However, completely amorphous glassy structures are not ideal in practical applications: although amorphous regions facilitate lithium ion migration, the mechanical strength of such materials is relatively poor due to the lack of a regular crystal framework, and there may be limitations in terms of ion migration uniformity and thermal stability. Therefore, through subsequent medium-temperature heat treatment, the glassy sulfide undergoes a partial crystallization process. During this process, the sulfide structure in the local area begins to transform from an amorphous state to a crystalline state, forming a crystalline phase region with a certain degree of order, while the non-crystallized part remains amorphous, eventually forming a composite structure in which the crystalline phase and the glassy phase coexist. In this composite structure, the crystalline phase provides a stable framework, and its regular lattice arrangement provides a continuous and efficient channel for lithium ion migration, significantly improving the overall ionic conductivity of the material. At the same time, the presence of the crystalline structure enhances the mechanical strength and thermal stability of the material, avoiding the brittleness problem of the glassy material during use.

[0082] The glass phase plays an important complementary role in the composite structure. Since the glassy region retains the characteristics of amorphous materials, its high degree of freedom provides more migration paths for lithium ions, while alleviating the possible interface impedance problems between crystalline phases. In the composite material, the presence of the glass phase effectively improves the continuity of ion transmission between crystalline phases and ensures the high-flux migration of lithium ions in the entire material. In addition, the flexible properties of the glass phase alleviate the internal stress of the material caused by volume changes during the electrochemical cycle to a certain extent, thereby further improving the mechanical stability and long-term service life of the material. The synergistic effect of the crystalline phase and the glass phase enables the composite material to have both the high ionic conductivity of the crystalline phase and the flexible characteristics of the glass phase, ultimately achieving an optimized balance between ionic conductivity and mechanical properties.

[0083] In the present invention, the inorganic core body is compounded with the inorganic phase precursor, and the inorganic core body plays an important role of "seed" or "template" in this process. In the subsequent ball milling and heat treatment steps, the inorganic core body induces the directional crystallization of the inorganic phase precursor through its own crystal structure. This process of induced crystallization can be understood as a "heterogeneous nucleation" mechanism, in which the crystal face of the inorganic core body provides a nucleation site for the crystallization of the inorganic phase precursor. Compared with the system without a core body, this nucleation method significantly reduces the nucleation energy barrier of the inorganic phase material, accelerates the crystallization process, and makes the crystallization more uniform and orderly. The introduction of this mechanism helps to avoid a large number of grain boundaries and structural defects that may be generated during the random crystallization process, thereby improving the overall structural integrity of the composite material.

[0084] During the ball milling process, the inorganic core body not only induces directional crystallization of the inorganic phase precursor through its crystal face, but also further evenly disperses the inorganic phase precursor components under mechanical action to ensure sufficient contact between the two. The subsequent heat treatment step further promotes the crystallization of the inorganic phase precursor and strengthens the interface bonding between the inorganic core body and the inorganic phase precursor. The final composite inorganic phase is a multi-scale multi-phase composite structure that has the advantages of both the crystalline phase and the glass phase. Specifically, the crystalline phase provides an efficient lithium ion migration channel, and its regular crystal structure provides a stable path for the large-scale migration of lithium ions within the material; while the glass phase provides a lower impedance for lithium ion transmission at the interface through its amorphous region, significantly enhancing the conductivity of the material at the multi-phase interface.

[0085] The formation of this multi-phase composite structure not only improves the lithium ion conductivity of the material, but also significantly improves its mechanical properties and cycle stability. On the one hand, the presence of the crystalline phase enables the composite material to maintain a high structural integrity during use, reducing structural damage caused by external stress or volume change; on the other hand, the inorganic core body acts as a seed, inducing uniform crystallization to effectively alleviate the internal stress that may be generated during the crystallization process, thereby improving the mechanical stability and thermal stability of the material. In addition, this multi-scale composite structure enables the material to form a continuous ion conduction network at different scales, further enhancing the diffusion capacity of lithium ions.

[0086] The present invention carries out multi-stage surface modification to the prepared composite inorganic phase to further improve its chemical stability, interfacial compatibility and overall electrochemical performance. In the first stage modification, indium trichloride and lithium chloride are selected as metal precursors, and the metal cations (In3+, Li+) are uniformly dispersed by dissolving them in anhydrous ethanol and regulating the pH value of the solution. The process of adjusting pH is crucial for the stability of the precursor solution. The appropriate acidic environment can prevent the premature precipitation of metal ions, while promoting the uniform interaction between them and solvent molecules to form a stable metal chloride precursor solution. This uniformly distributed solution lays the foundation for the subsequent coating process. On the surface of the composite inorganic phase, the metal chloride in the precursor solution is uniformly distributed by deposition, gradually forming a dense and uniform coating layer. Subsequently, by appropriate heat treatment, the coating layer is solidified and partially crystallized, and finally forms an inorganic shell with high chemical stability.

[0087] The introduction of this coating layer significantly optimizes the material properties in many aspects. First, the coating layer effectively passivates the surface chemical activity of the sulfide composite inorganic phase. Sulfide materials are usually highly sensitive to moisture and oxygen in the air, and are prone to hydrolysis or oxidation reactions, resulting in rapid degradation of performance. By coating with a dense metal chloride shell, the sulfide can be effectively isolated from direct contact with the external environment, significantly improving the environmental stability and storage life of the material. Secondly, the coating layer reduces the interfacial impedance by optimizing the interfacial compatibility between the composite inorganic phase and the subsequent polymer matrix. This is because the introduction of the metal chloride layer can adjust the physicochemical properties of the inorganic phase surface, making it easier to form a good interfacial contact with the polymer, thereby improving the conductivity and stability of the overall material.

[0088] On the basis of the first coating layer, the present invention further carries out a modified design of the second coating layer. In this stage, ammonium fluoride and lithium acetate are reacted in anhydrous ethanol to generate a lithium fluoride precursor. On the surface of the composite inorganic phase, lithium fluoride is uniformly covered on the first coating layer by chemical deposition to form a second layer of protective barrier. Subsequently, through moderate heat treatment, the lithium fluoride layer is further solidified and forms a stable structure. Lithium fluoride is a material with low electronic conductivity and high chemical stability, which plays a further chemical protection role in the coating system. Compared with the first coating layer, the lithium fluoride layer can more effectively resist the intrusion of moisture and oxygen in the environment, while providing a stronger chemical isolation effect on the sulfide inorganic phase. Therefore, the introduction of the double-layer coating structure greatly improves the environmental stability and durability of the composite inorganic phase.

[0089] On the basis of double-layer coating, the present invention further introduces a conductive layer to improve the overall electrochemical properties of the material. Polyaniline is uniformly coated on the surface of the double-layer coated inorganic phase to form a conductive shell. Polyaniline is a conductive polymer with good electronic conductivity. The conjugated system in its structure allows electrons to move freely in the molecular chain, thereby significantly improving the electronic conductivity of the composite material. The introduction of the polyaniline layer plays multiple roles in the composite inorganic phase: on the one hand, it provides an additional electron conduction path for the composite material, significantly reducing the interface impedance between the inorganic phase and the electrode; on the other hand, the flexibility and chemical stability of polyaniline can also enhance the structural stability of the material during the cycle process and improve its electrochemical reaction kinetics during multiple charge and discharge processes. In addition, polyaniline can also interact with the inorganic phase and the electrolyte interface through the polar groups on its surface, further optimizing the interface contact state.

[0090] The final three-layer structural system, i.e., the composite coating structure consisting of the first layer of metal chloride, the second layer of lithium fluoride, and the third layer of conductive polyaniline, exhibits significant performance advantages. The lithium fluoride layer acts as an intermediate chemical protection barrier, providing excellent environmental stability and preventing the composite inorganic phase from being corroded by the outside world; while the polyaniline layer further optimizes the overall performance of the material by improving electronic conductivity and interfacial electrochemical properties. The synergistic effect of this dual protection and the introduction of conductivity enables the composite inorganic phase to exhibit higher cycle stability and excellent electrochemical performance in the solid electrolyte system, ultimately providing a reliable material foundation and solution for the application of high-performance solid-state lithium batteries.

[0091] In this study, in order to further optimize the performance of polyetheretherketone to meet the application requirements of solid electrolytes, it was modified in multiple steps, so that its ionic conductivity, flexibility and mechanical stability were significantly improved. First, sulfonic acid groups were introduced into the molecular skeleton of polyetheretherketone through sulfonation reaction. In this process, the sulfonic acid groups were uniformly grafted onto the polymer chain by the electrophilic substitution reaction of the sulfonation reagent and the aromatic ring in polyetheretherketone. The sulfonic acid group has strong polarity and high affinity for lithium ions. Its introduction significantly enhances the interaction between the polymer and lithium ions, thereby improving the migration ability of lithium ions. In addition, the presence of sulfonic acid groups also destroys the regularity of the polyetheretherketone molecular chain, reduces the crystallinity of the polymer, and increases the proportion of amorphous regions. The amorphous region provides more molecular freedom, forming a low-impedance path for the migration of lithium ions in the polymer matrix, thereby significantly improving the ionic conductivity of the material.

[0092] In order to further improve the flexibility and ion transport properties of the polymer, polyethylene glycol segments were introduced on the basis of sulfonated polyetheretherketone. Polyethylene glycol is a flexible polymer. Its low glass transition temperature and the degree of freedom of the polymer chain can significantly reduce the crystallinity of the polymer and further expand the proportion of the amorphous region. By introducing polyethylene glycol segments into the molecular skeleton of sulfonated polyetheretherketone through chemical grafting or copolymerization, it not only improves the flexibility and deformation ability of the polymer, but also gives the material a higher ion migration ability. The ether radicals in the polyethylene glycol segments can form a dynamic coordination effect with lithium ions, further reducing the activation energy of lithium ion migration, thereby accelerating the diffusion process of ions in the polymer.

[0093] On this basis, the overall performance of the material was further optimized by cross-linking. The cross-linking process introduces chemical bonds between polymer molecular chains through chemical reactions to construct a three-dimensional network structure. This three-dimensional cross-linked network not only improves the mechanical properties of the film, but also significantly enhances the shape retention ability of the material, enabling it to resist the influence of external stress and volume changes during electrochemical cycles. In addition, the introduction of the cross-linked structure can also limit the excessive movement of the molecular chain segments, thereby ensuring the ion conductivity while avoiding the deformation failure problem caused by excessive softness of the material. The polymer film finally prepared not only exhibits excellent ion conductivity, but also has high flexibility and excellent mechanical stability.

[0094] In this experimental scheme, a solid electrolyte system with excellent comprehensive performance was constructed by compounding the inorganic phase with the polymer matrix. The inorganic phase and the polymer matrix respectively assume different functions in the material, and the synergistic enhancement of performance is achieved through ingenious structural design. As the main component of the solid electrolyte, the inorganic phase has high lithium ion mobility, and its partially crystallized structure provides a regular and efficient lithium ion migration channel, which significantly reduces the diffusion impedance of lithium ions in the solid electrolyte. At the same time, the residual amorphous region in the inorganic phase effectively alleviates the ion migration barrier caused by the grain boundary effect and maintains the uniformity of the overall ion conduction of the material. In addition, inorganic sulfide materials provide a solid foundation for composite electrolytes due to their unique chemical stability and high conductivity.

[0095] On the other hand, the polymer matrix provides mechanical support and flexible adjustment functions for the composite material by filling the gaps between the inorganic phases. The amorphous region of the polymer acts as a dynamic channel for lithium ion migration. It can not only form a good interface contact with the inorganic phase, but also flexibly fill the gaps between the inorganic phases, thereby avoiding the ion migration impedance problem caused by interface discontinuity or physical defects. The presence of the polymer matrix also gives the composite electrolyte excellent deformation ability and processing properties, enabling it to adapt to complex electrode structures. In addition, the chemical adjustability of polymer materials also provides the possibility of further optimizing interface compatibility and mechanical properties.

[0096] Through the organic combination of the two materials, the inorganic phase and the polymer, a "double continuous ion conductive network" structure is formed. In this network, the inorganic phase constructs the main lithium ion migration channel through its highly conductive crystalline phase region, while the polymer matrix connects and fills the interface region of the inorganic phase through its flexible amorphous region, forming a continuous and uniform ion migration path. The biggest advantage of the double continuous network structure is that the inorganic phase and the polymer phase respectively play their respective functional characteristics, while achieving synergistic effects at the interface. This design effectively avoids the problems of interface instability and uneven ion migration that may exist in traditional composite electrolytes, thereby significantly improving the overall electrochemical performance of the composite electrolyte.

[0097] In the preparation process of the composite material, a heat-induced cross-linking process was further introduced to construct a three-dimensional network structure in the polymer matrix through a chemical cross-linking reaction. The formation of the three-dimensional cross-linked network not only significantly enhances the mechanical strength and shape retention ability of the polymer matrix, but also improves the bonding strength of the polymer and inorganic phase interface. This three-dimensional network structure significantly improves the structural stability of the composite material while maintaining the flexibility of the material by limiting the excessive movement of the polymer chain segments. In addition, the presence of the cross-linked network can effectively inhibit the fluidity of the polymer under high temperature or long-term operation conditions, thereby enhancing the thermal stability and cycle life of the composite electrolyte.

[0098] Compared with the prior art, the present invention has the following beneficial effects:

[0099] (1) A partially crystallized sulfide network is generated through the mechanochemical reaction of lithium sulfide and phosphorus pentasulfide, and high-valent metal ions are doped to optimize the lattice structure, reduce the energy barrier for lithium ion migration, and enhance conductivity and chemical stability. The crystalline phase provides an efficient lithium ion migration channel, and the amorphous region reduces the grain boundary effect and improves the uniformity of ion conduction;

[0100] (2) The performance of the inorganic phase is improved by coating. The metal chloride and lithium fluoride coating layers isolate the moisture and oxygen in the environment, greatly improving the environmental stability and durability of the composite inorganic phase; the polyaniline coating significantly reduces the interfacial impedance of the inorganic phase. At the same time, the flexibility and chemical stability of polyaniline can also enhance the structural stability of the material during the cycle process;

[0101] (3) Sulfonated polyetheretherketone introduces sulfonic acid groups to improve its lithium affinity, reduce crystallinity and increase amorphous regions, providing a low impedance path for lithium ion migration. Polyethylene glycol segments enhance flexibility and ion migration capabilities, cross-link to form a three-dimensional network structure, and further improve mechanical strength and interface stability;

[0102] (4) The inorganic phase provides a highly conductive main channel, and the polymer flexibly fills the gaps between the inorganic phases to form a double continuous ion conductive network. The coating layer and the conductive polymer are combined to reduce the interface impedance, optimize the ion transport path and interface chemical properties. The inorganic phase and the polymer work synergistically to improve conductivity, mechanical properties and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0103] Figure 1 A flow chart of a preparation method of a sulfide-polymer composite solid electrolyte provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0104] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0105] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products without further purification or treatment.

[0106] Example 1

[0107] This embodiment provides a sulfide-polymer composite solid electrolyte and a preparation method thereof, wherein the preparation method specifically comprises the following steps:

[0108] S1: The mixed powder obtained by ball milling the sulfide and the inorganic salt is heat treated in an argon atmosphere to obtain an inorganic core body;

[0109] Specifically, S1: sulfide lithium sulfide and phosphorus pentasulfide are mixed with lanthanum trichloride, gallium chloride, and aluminum trichloride and ball-milled to obtain a mixed powder, wherein the molar ratio of lithium sulfide to phosphorus pentasulfide is 7.6:3, and the molar ratio of sulfide to inorganic salt is 1:0.11; the mixed powder is heat-treated in an argon atmosphere to obtain an inorganic core body, wherein the heating rate of the heat treatment is 8°C / min, the temperature is 370°C, and the time is 2.7h;

[0110] S2: melting lithium sulfide and phosphorus pentasulfide, cooling them, and then heat treating them to obtain an inorganic phase precursor; mixing the inorganic phase precursor with the inorganic core body and heat treating them to obtain a composite inorganic phase;

[0111] Specifically, S2: lithium sulfide and phosphorus pentasulfide are melted at a molar ratio of 2.4:1 in an argon atmosphere at a temperature of 580°C for 18 minutes, and then cooled to obtain a glass precursor, which is heat-treated at 280°C for 3 hours to obtain an inorganic phase precursor; the inorganic phase precursor and the inorganic core body are mixed and ball-milled at a mass ratio of 8.5:1, and then heat-treated at 340°C for 1 hour to obtain a composite inorganic phase;

[0112] S3: dissolving indium trichloride and lithium chloride in anhydrous ethanol, adding acetic acid and then refluxing to obtain a precursor solution, reacting the composite inorganic phase with the precursor solution, and subjecting the composite inorganic phase to a heat treatment to obtain a first coating inorganic phase;

[0113] Specifically, S3: indium trichloride and lithium chloride are dissolved in anhydrous ethanol at a molar ratio of 1:3, wherein the concentration of indium trichloride is 0.2M, acetic acid is added to adjust the pH to 4.8, and refluxed at 55°C for 2.7h to obtain a precursor solution; the composite inorganic phase is dispersed in anhydrous ethanol with a mass fraction of 5.8wt.% to obtain a composite inorganic phase dispersion, the precursor solution is dripped into it at a constant temperature of 67°C and stirred for 4.5h, wherein the mass ratio of the composite inorganic phase to the precursor solution is 1:10, centrifuged, washed, and heat treated at 270°C for 2h in an argon atmosphere to obtain a first coated inorganic phase;

[0114] S4: dispersing ammonium fluoride and lithium acetate in anhydrous ethanol to obtain a second precursor solution, reacting the first coating inorganic phase with the second precursor solution, and subjecting the reaction to heat treatment to obtain a double-layer coating product; compounding polyaniline with the double-layer coating product to obtain a conductive layer coating inorganic phase;

[0115] Specifically, S4: ammonium fluoride and lithium acetate are dispersed in anhydrous ethanol to obtain a second precursor solution, wherein the concentration of ammonium fluoride is 0.28 mol / L and the concentration of ammonium fluoride is 0.28 mol / L; the first coating inorganic phase is dispersed in anhydrous ethanol with a mass fraction of 3.4 wt% to obtain dispersion A, the second precursor solution is added dropwise and stirred at 50°C for 2 hours, wherein the mass ratio of the first coating inorganic phase to the second precursor solution is 1:8, centrifuged, washed, and heat treated at 157°C under an argon atmosphere for 1 hour to obtain a double-layer coated inorganic phase; polyaniline is dispersed in N-methylpyrrolidone with a mass fraction of 2.6 wt.% to obtain dispersion B, the double-layer coated inorganic phase is added to the dispersion B and stirred at room temperature for 4.5 hours, wherein the mass ratio of the double-layer coated inorganic phase to polyaniline is 97:3, centrifuged, washed, and dried to obtain a conductive layer coated inorganic phase.

[0116] S5: dispersing polyetheretherketone in concentrated sulfuric acid to obtain sulfonated polyetheretherketone, and reacting the sulfonated polyetheretherketone with methoxy polyethylene glycol to obtain a modified polymer;

[0117] Specifically, S5: disperse polyetheretherketone in concentrated sulfuric acid at a mass fraction of 4.8wt.%, stir at 40°C for 10h, slowly pour the reaction solution into ice water, filter, wash, and vacuum dry to obtain sulfonated polyetheretherketone; disperse it in N,N-dimethylformamide at a mass fraction of 13wt.%, add 1.6M sodium hydroxide solution to adjust the pH to 8.7, dropwise add 17wt.% of methoxypolyethylene glycol in N,N-dimethylformamide solution, wherein the mass ratio of methoxypolyethylene glycol to sulfonated polyetheretherketone is 1.8:1, react at 70°C for 22h to obtain a reaction solution, pour the reaction solution into deionized water, filter, wash, and dry to obtain a modified polymer;

[0118] S6: Dispersing the modified polymer in N,N-dimethylformamide, adding a conductive layer-coated inorganic phase, a cross-linking agent, an initiator and a lithium salt, and mixing to obtain a uniform mixed solution, and casting the film to obtain a composite solid electrolyte by cross-linking.

[0119] Specifically, S6: Disperse the modified polymer in N,N-dimethylformamide at a mass fraction of 14wt.%, add polyethylene glycol dimethacrylate and azobisisobutyronitrile, wherein the mass ratio of polyethylene glycol dimethacrylate to the modified polymer is 0.25:1, and the amount of azobisisobutyronitrile is 0.1% of the mass of polyethylene glycol dimethacrylate, and ultrasonically disperse to obtain a polymer solution; disperse the conductive layer coated inorganic phase in N,N-dimethylformamide at a mass fraction of 16wt.%, add the polymer solution, and then add lithium perchlorate, and evenly disperse to obtain a uniform mixed solution, wherein the concentration of lithium perchlorate in the uniform mixed solution is 0.2M, and the mass ratio of the modified polymer to the conductive layer coated inorganic phase is 30:70. After cast film formation, pre-dry at 88°C for 2.8h, thermally induce crosslinking at 125°C for 2.8h, and vacuum dry to obtain a sulfide-polymer composite solid electrolyte.

[0120] Example 2

[0121] This embodiment provides a sulfide-polymer composite solid electrolyte and a preparation method thereof, wherein the preparation method specifically comprises the following steps:

[0122] S1: The mixed powder obtained by ball milling the sulfide and the inorganic salt is heat treated in an argon atmosphere to obtain an inorganic core body;

[0123] Specifically, S1: sulfide lithium sulfide and phosphorus pentasulfide are mixed with gallium chloride and aluminum chloride and ball-milled to obtain a mixed powder, wherein the molar ratio of lithium sulfide to phosphorus pentasulfide is 8:3, and the molar ratio of sulfide to inorganic salt is 1:0.15; the mixed powder is heat-treated in an argon atmosphere to obtain an inorganic core body, wherein the heating rate of the heat treatment is 5°C / min, the temperature is 400°C, and the time is 2.3h;

[0124] S2: melting lithium sulfide and phosphorus pentasulfide, cooling them, and then heat treating them to obtain an inorganic phase precursor; mixing the inorganic phase precursor with the inorganic core body and heat treating them to obtain a composite inorganic phase;

[0125] Specifically, S2: lithium sulfide and phosphorus pentasulfide are melted at a molar ratio of 2.3:1 in an argon atmosphere at a temperature of 590°C for 15 minutes, and then cooled to obtain a glass precursor, which is heat-treated at 270°C for 2.3 hours to obtain an inorganic phase precursor; the inorganic phase precursor and the inorganic core body are mixed and ball-milled at a mass ratio of 9:1, and then heat-treated at 380°C for 2 hours to obtain a composite inorganic phase;

[0126] S3: dissolving indium trichloride and lithium chloride in anhydrous ethanol, adding acetic acid and then refluxing to obtain a precursor solution, reacting the composite inorganic phase with the precursor solution, and subjecting the composite inorganic phase to a heat treatment to obtain a first coating inorganic phase;

[0127] Specifically, S3: Indium trichloride and lithium chloride are dissolved in anhydrous ethanol at a molar ratio of 1:3, 1:4, 1:3, and 1:4, wherein the concentration of indium trichloride is 0.2M, 0.3M, 0.1M, and 0.23M, and acetic acid is added to adjust the pH to 4.8, 4.5, 4, and 5, and reflux at 55°C, 60°C, 50°C, and 58°C for 2.7h, 2.3h, 2h, and 3h to obtain a precursor solution; the composite inorganic phase is dispersed in anhydrous ethanol with a mass fraction of 5.6wt.% to obtain a composite inorganic phase dispersion, and the precursor solution is dropped at a constant temperature of 63°C and stirred for 4.9h, wherein the mass ratio of the composite inorganic phase to the precursor solution is 1:11, centrifuged, washed, and heat treated at 280°C in an argon atmosphere for 1.8h to obtain a first coated inorganic phase;

[0128] S4: dispersing ammonium fluoride and lithium acetate in anhydrous ethanol to obtain a second precursor solution, reacting the first coating inorganic phase with the second precursor solution, and subjecting the reaction to heat treatment to obtain a double-layer coating product; compounding polyaniline with the double-layer coating product to obtain a conductive layer coating inorganic phase;

[0129] Specifically, S4: ammonium fluoride and lithium acetate are dispersed in anhydrous ethanol to obtain a second precursor solution, wherein the concentration of ammonium fluoride is 0.24 mol / L and the concentration of ammonium fluoride is 0.24 mol / L; the first coating inorganic phase is dispersed in anhydrous ethanol with a mass fraction of 3.8 wt.% to obtain dispersion A, the second precursor solution is added dropwise and stirred at 60°C for 3 hours, wherein the mass ratio of the first coating inorganic phase to the second precursor solution is 1:9, centrifuged, washed, and heat treated at 156°C under an argon atmosphere for 2 hours to obtain a double-layer coated inorganic phase; polyaniline is dispersed in N-methylpyrrolidone with a mass fraction of 2.3 wt.% to obtain dispersion B, the double-layer coated inorganic phase is added to the dispersion B and stirred at room temperature for 5 hours, wherein the mass ratio of the double-layer coated inorganic phase to polyaniline is 96:4, centrifuged, washed, and dried to obtain a conductive layer coated inorganic phase.

[0130] S5: dispersing polyetheretherketone in concentrated sulfuric acid to obtain sulfonated polyetheretherketone, and reacting the sulfonated polyetheretherketone with methoxy polyethylene glycol to obtain a modified polymer;

[0131] Specifically, S5: disperse polyetheretherketone in concentrated sulfuric acid at a mass fraction of 4.5wt.%, stir at 50°C for 12h, slowly pour the reaction solution into ice water, filter, wash, and vacuum dry to obtain sulfonated polyetheretherketone; disperse it in N,N-dimethylformamide at a mass fraction of 14wt.%, add 1.2M sodium hydroxide solution to adjust the pH to 8.9, dropwise add 16wt.% of methoxypolyethylene glycol in N,N-dimethylformamide solution, wherein the mass ratio of methoxypolyethylene glycol to sulfonated polyetheretherketone is 2:1, react at 80°C for 23h to obtain a reaction solution, pour the reaction solution into deionized water, filter, wash, and dry to obtain a modified polymer;

[0132] S6: Dispersing the modified polymer in N,N-dimethylformamide, adding a conductive layer-coated inorganic phase, a cross-linking agent, an initiator and a lithium salt, and mixing to obtain a uniform mixed solution, and casting the film to obtain a composite solid electrolyte by cross-linking.

[0133] Specifically, S6: Disperse the modified polymer in N,N-dimethylformamide at a mass fraction of 15wt.%, add polyethylene glycol dimethacrylate and azobisisobutyronitrile, wherein the mass ratio of polyethylene glycol dimethacrylate to the modified polymer is 0.28:1, and the amount of azobisisobutyronitrile is 0.05% of the mass of polyethylene glycol dimethacrylate, and ultrasonically disperse to obtain a polymer solution; disperse the conductive layer coated inorganic phase in N,N-dimethylformamide at a mass fraction of 18wt.%, add the polymer solution, and then add lithium tetrafluoroborate, and evenly disperse to obtain a uniform mixed solution, wherein the concentration of lithium tetrafluoroborate in the uniform mixed solution is 0.28M, and the mass ratio of the modified polymer to the conductive layer coated inorganic phase is 35:65. After cast film formation, pre-dry at 84°C for 2.3h, thermally induce crosslinking at 128°C for 2.5h, and vacuum dry to obtain a sulfide-polymer composite solid electrolyte.

[0134] Example 3

[0135] This embodiment provides a sulfide-polymer composite solid electrolyte and a preparation method thereof, wherein the preparation method specifically comprises the following steps:

[0136] S1: The mixed powder obtained by ball milling the sulfide and the inorganic salt is heat treated in an argon atmosphere to obtain an inorganic core body;

[0137] Specifically, S1: sulfide lithium sulfide and phosphorus pentasulfide are mixed with lanthanum trichloride and aluminum trichloride and ball-milled to obtain a mixed powder, wherein the molar ratio of lithium sulfide to phosphorus pentasulfide is 7:3, and the molar ratio of sulfide to inorganic salt is 1:0.05; the mixed powder is heat-treated in an argon atmosphere to obtain an inorganic core body, wherein the heating rate of the heat treatment is 7°C / min, the temperature is 300°C, and the time is 2h;

[0138] S2: melting lithium sulfide and phosphorus pentasulfide, cooling them, and then heat treating them to obtain an inorganic phase precursor; mixing the inorganic phase precursor with the inorganic core body and heat treating them to obtain a composite inorganic phase;

[0139] Specifically, S2: lithium sulfide and phosphorus pentasulfide are melted at a molar ratio of 2:1 in an argon atmosphere at a temperature of 550°C for 10 minutes, and then cooled to obtain a glass precursor, which is heat-treated at 250°C for 2 hours to obtain an inorganic phase precursor; the inorganic phase precursor and the inorganic core body are mixed and ball-milled at a mass ratio of 8:1, and then heat-treated at 300°C for 1.8 hours to obtain a composite inorganic phase;

[0140] S3: dissolving indium trichloride and lithium chloride in anhydrous ethanol, adding acetic acid and then refluxing to obtain a precursor solution, reacting the composite inorganic phase with the precursor solution, and subjecting the composite inorganic phase to a heat treatment to obtain a first coating inorganic phase;

[0141] Specifically, S3: dissolving indium trichloride and lithium chloride in anhydrous ethanol at a molar ratio of 1:3, wherein the concentration of indium trichloride is 0.1M, adding acetic acid to adjust the pH to 4, and reflux at 50°C for 2h to obtain a precursor solution; dispersing the composite inorganic phase in anhydrous ethanol with a mass fraction of 5wt.% to obtain a composite inorganic phase dispersion, dripping the precursor solution at a constant temperature of 60°C and stirring for 4h, wherein the mass ratio of the composite inorganic phase to the precursor solution is 1:8, centrifuging, washing, and heat treating at 250°C for 1.2h in an argon atmosphere to obtain a first coated inorganic phase;

[0142] S4: dispersing ammonium fluoride and lithium acetate in anhydrous ethanol to obtain a second precursor solution, reacting the first coating inorganic phase with the second precursor solution, and subjecting the reaction to heat treatment to obtain a double-layer coating product; compounding polyaniline with the double-layer coating product to obtain a conductive layer coating inorganic phase;

[0143] Specifically, S4: ammonium fluoride and lithium acetate are dispersed in anhydrous ethanol to obtain a second precursor solution, wherein the concentration of ammonium fluoride is 0.2 mol / L and the concentration of ammonium fluoride is 0.2 mol / L; the first coating inorganic phase is dispersed in anhydrous ethanol with a mass fraction of 4 wt.% to obtain dispersion A, the second precursor solution is added dropwise and stirred at 58°C for 2.7 hours, wherein the mass ratio of the first coating inorganic phase to the second precursor solution is 1:6, centrifuged, washed, and heat treated at 150°C under an argon atmosphere for 1.7 hours to obtain a double-layer coated inorganic phase; polyaniline is dispersed in N-methylpyrrolidone with a mass fraction of 2 wt.% to obtain dispersion B, the double-layer coated inorganic phase is added to the dispersion B and stirred at room temperature for 5 hours, wherein the mass ratio of the double-layer coated inorganic phase to polyaniline is 95:5, centrifuged, washed, and dried to obtain a conductive layer coated inorganic phase.

[0144] S5: dispersing polyetheretherketone in concentrated sulfuric acid to obtain sulfonated polyetheretherketone, and reacting the sulfonated polyetheretherketone with methoxy polyethylene glycol to obtain a modified polymer;

[0145] Specifically, S5: disperse polyetheretherketone in concentrated sulfuric acid at a mass fraction of 4wt.%, stir at 47°C for 11h, slowly pour the reaction solution into ice water, filter, wash, and vacuum dry to obtain sulfonated polyetheretherketone; disperse it in N,N-dimethylformamide at a mass fraction of 10wt.%, add 1M sodium hydroxide solution to adjust the pH to 8, dropwise add 15wt.% of methoxypolyethylene glycol in N,N-dimethylformamide solution, wherein the mass ratio of methoxypolyethylene glycol to sulfonated polyetheretherketone is 1:1, react at 77°C for 20h to obtain a reaction solution, pour the reaction solution into deionized water, filter, wash, and dry to obtain a modified polymer;

[0146] S6: Dispersing the modified polymer in N,N-dimethylformamide, adding a conductive layer-coated inorganic phase, a cross-linking agent, an initiator and a lithium salt, and mixing to obtain a uniform mixed solution, and casting the film to obtain a composite solid electrolyte by cross-linking.

[0147] Specifically, S6: Disperse the modified polymer in N,N-dimethylformamide at a mass fraction of 10wt.%, add polyethylene glycol dimethacrylate and azobisisobutyronitrile, wherein the mass ratio of polyethylene glycol dimethacrylate to the modified polymer is 0.2:1, and the amount of azobisisobutyronitrile is 0.12% of the mass of polyethylene glycol dimethacrylate, and ultrasonically disperse to obtain a polymer solution; disperse the conductive layer coated inorganic phase in N,N-dimethylformamide at a mass fraction of 15wt.%, add the polymer solution, and then add lithium perchlorate, and evenly disperse to obtain a uniform mixed solution, wherein the concentration of lithium perchlorate in the uniform mixed solution is 0.1M, and the mass ratio of the modified polymer to the conductive coated inorganic phase is 20:80. After cast film formation, pre-dry at 80°C for 2h, heat-induced crosslinking at 120°C for 2h, and vacuum dry to obtain a sulfide-polymer composite solid electrolyte.

[0148] Example 4

[0149] This embodiment provides a sulfide-polymer composite solid electrolyte and a preparation method thereof, wherein the preparation method specifically comprises the following steps:

[0150] S1: The mixed powder obtained by ball milling the sulfide and the inorganic salt is heat treated in an argon atmosphere to obtain an inorganic core body;

[0151] Specifically, S1: sulfide lithium sulfide and phosphorus pentasulfide are mixed with lanthanum trichloride and gallium chloride and ball-milled to obtain a mixed powder, wherein the molar ratio of lithium sulfide to phosphorus pentasulfide is 7.8:3, and the molar ratio of sulfide to inorganic salt is 1:0.13; the mixed powder is heat-treated in an argon atmosphere to obtain an inorganic core body, wherein the heating rate of the heat treatment is 10°C / min, the temperature is 340°C, and the time is 3h;

[0152] S2: melting lithium sulfide and phosphorus pentasulfide, cooling them, and then heat treating them to obtain an inorganic phase precursor; mixing the inorganic phase precursor with the inorganic core body and heat treating them to obtain a composite inorganic phase;

[0153] Specifically, S2: lithium sulfide and phosphorus pentasulfide are melted at a molar ratio of 2.5:1 in an argon atmosphere at a temperature of 600°C for 20 minutes, and then cooled to obtain a glass precursor, which is heat-treated at 300°C for 2.9 hours to obtain an inorganic phase precursor; the inorganic phase precursor and the inorganic core body are mixed and ball-milled at a mass ratio of 8.9:1, and then heat-treated at 400°C for 1.2 hours to obtain a composite inorganic phase;

[0154] S3: dissolving indium trichloride and lithium chloride in anhydrous ethanol, adding acetic acid and then refluxing to obtain a precursor solution, reacting the composite inorganic phase with the precursor solution, and subjecting the composite inorganic phase to a heat treatment to obtain a first coating inorganic phase;

[0155] Specifically, S3: dissolving indium trichloride and lithium chloride in anhydrous ethanol at a molar ratio of 1:4, wherein the concentration of indium trichloride is 0.23M, adding acetic acid to adjust the pH to 5, and reflux at 58°C for 3h to obtain a precursor solution; dispersing the composite inorganic phase in anhydrous ethanol with a mass fraction of 6wt.% to obtain a composite inorganic phase dispersion, dripping the precursor solution at a constant temperature of 70°C and stirring for 5h, wherein the mass ratio of the composite inorganic phase to the precursor solution is 1:12, centrifuging, washing, and heat treating at 300°C for 1h in an argon atmosphere to obtain a first coated inorganic phase;

[0156] S4: dispersing ammonium fluoride and lithium acetate in anhydrous ethanol to obtain a second precursor solution, reacting the first coating inorganic phase with the second precursor solution, and subjecting the reaction to heat treatment to obtain a double-layer coating product; compounding polyaniline with the double-layer coating product to obtain a conductive layer coating inorganic phase;

[0157] Specifically, S4: ammonium fluoride and lithium acetate are dispersed in anhydrous ethanol to obtain a second precursor solution, wherein the concentration of ammonium fluoride is 0.3 mol / L and the concentration of ammonium fluoride is 0.3 mol / L; the first coating inorganic phase is dispersed in anhydrous ethanol with a mass fraction of 3 wt.% to obtain dispersion A, the second precursor solution is added dropwise and stirred at 56°C for 2.3 hours, wherein the mass ratio of the first coating inorganic phase to the second precursor solution is 1:10, centrifuged, washed, and heat treated at 160°C under an argon atmosphere for 1.2 hours to obtain a double-layer coated inorganic phase; polyaniline is dispersed in N-methylpyrrolidone with a mass fraction of 3 wt.% to obtain dispersion B, the double-layer coated inorganic phase is added to the dispersion B and stirred at room temperature for 4.9 hours, wherein the mass ratio of the double-layer coated inorganic phase to polyaniline is 98:2, centrifuged, washed, and dried to obtain a conductive layer coated inorganic phase.

[0158] S5: dispersing polyetheretherketone in concentrated sulfuric acid to obtain sulfonated polyetheretherketone, and reacting the sulfonated polyetheretherketone with methoxy polyethylene glycol to obtain a modified polymer;

[0159] Specifically, S5: disperse polyetheretherketone in concentrated sulfuric acid at a mass fraction of 5wt.%, stir at 45°C for 11.2h, slowly pour the reaction solution into ice water, filter, wash, and vacuum dry to obtain sulfonated polyetheretherketone; disperse it in N,N-dimethylformamide at a mass fraction of 15wt.%, add 2M sodium hydroxide solution to adjust the pH to 9, dropwise add 20wt.% of methoxypolyethylene glycol in N,N-dimethylformamide solution, wherein the mass ratio of methoxypolyethylene glycol to sulfonated polyetheretherketone is 1.6:1, react at 78°C for 24h to obtain a reaction solution, pour the reaction solution into deionized water, filter, wash, and dry to obtain a modified polymer;

[0160] S6: Dispersing the modified polymer in N,N-dimethylformamide, adding a conductive layer-coated inorganic phase, a cross-linking agent, an initiator and a lithium salt, and mixing to obtain a uniform mixed solution, and casting the film to obtain a composite solid electrolyte by cross-linking.

[0161] Specifically, S6: Disperse the modified polymer in N,N-dimethylformamide at a mass fraction of 12wt.%, add polyethylene glycol dimethacrylate and azobisisobutyronitrile, wherein the mass ratio of polyethylene glycol dimethacrylate to the modified polymer is 0.3:1, and the amount of azobisisobutyronitrile is 0.15% of the mass of polyethylene glycol dimethacrylate, and ultrasonically disperse to obtain a polymer solution; disperse the conductive layer coated inorganic phase in N,N-dimethylformamide at a mass fraction of 20wt.%, add the polymer solution, and then add lithium tetrafluoroborate, and evenly disperse to obtain a uniform mixed solution, wherein the concentration of lithium tetrafluoroborate in the uniform mixed solution is 0.3M, and the mass ratio of the modified polymer and the conductive layer coated inorganic phase is 40:60. After cast film formation, pre-dry at 90°C for 3h, heat-induced crosslinking at 130°C for 3h, and vacuum dry to obtain a sulfide-polymer composite solid electrolyte.

[0162] Comparative Example 1

[0163] This comparative example provides a sulfide-polymer composite solid electrolyte, which is different from Example 1 in that in S2, the mass ratio of the inorganic phase precursor to the inorganic core body is 10:1, and the other operating steps and process parameters are exactly the same as those in Example 1.

[0164] Comparative Example 2

[0165] This comparative example provides a sulfide-polymer composite solid electrolyte, which is different from Example 1 in that in S2, the mass ratio of the inorganic phase precursor to the inorganic core body is 5:1, and the other operating steps and process parameters are exactly the same as those in Example 1.

[0166] Comparative Example 3

[0167] This comparative example provides a sulfide-polymer composite solid electrolyte, which is different from Example 1 in that, in S4, the mass ratio of the double-layer coated inorganic phase to polyaniline is 92:8, and the other operating steps and process parameters are exactly the same as those in Example 1.

[0168] Comparative Example 4

[0169] This comparative example provides a sulfide-polymer composite solid electrolyte, which is different from Example 1 in that, in S4, the mass ratio of the double-layer coated inorganic phase to polyaniline is 99:1, and the other operating steps and process parameters are exactly the same as those in Example 1.

[0170] Comparative Example 5

[0171] This comparative example provides a sulfide-polymer composite solid electrolyte, which is different from Example 1 in that, in S5, the mass ratio of methoxy polyethylene glycol to sulfonated polyetheretherketone is 5:1, and the other operating steps and process parameters are exactly the same as those in Example 1.

[0172] Comparative Example 6

[0173] This comparative example provides a sulfide-polymer composite solid electrolyte, which is different from Example 1 in that in S5, the mass ratio of methoxy polyethylene glycol to sulfonated polyetheretherketone is 0.1:1, and the other operating steps and process parameters are exactly the same as those in Example 1.

[0174] The performance test of the sulfide-polymer composite solid electrolytes of Examples 1-4 and Comparative Examples 1-6 was performed, and the specific process is as follows:

[0175] Ionic conductivity: The samples were punched in an argon atmosphere and the ionic conductivity was tested by an impedance analyzer using a mold battery experiment. The test conditions were: test pressure 200MPa, frequency 35MHz-0.1Hz;

[0176] Tensile strength: Tested using a battery separator tensile strength tester.

[0177] The test results are shown in Table 1.

[0178] Table 1: Performance test results of sulfide-polymer composite solid electrolytes based on Examples 1-4 and Comparative Examples 1-6

[0179]

[0180]

[0181] From the test results of Example 1 and Comparative Examples 1 and 2, it can be seen that the content of inorganic phase precursor is too high, and the proportion of amorphous regions in the composite inorganic phase increases, which may lead to insufficient effective connectivity of the crystalline phase conductive channel, thereby reducing the ionic conductivity. In addition, the excess of inorganic phase may lead to poor inter-particle interface bonding, reduce the mechanical properties of the material, and weaken the tensile strength; the content of inorganic core body is too high, which will make the proportion of crystalline phase in the composite inorganic phase too high. Although more high-conductivity channels can be provided, the lack of amorphous regions will limit the uniform distribution and diffusion of lithium ions. At the same time, too much rigid crystalline phase will reduce the tensile strength of the material.

[0182] From the test results of Example 1 and Comparative Examples 3 and 4, it can be seen that an excess of polyaniline may lead to the formation of a thicker conductive layer on the electrolyte surface. Although this helps to reduce the interfacial impedance, it will hinder the effective migration of lithium ions and reduce the ionic conductivity. In addition, too much polyaniline will reduce the overall mechanical strength of the material because polyaniline is highly flexible and difficult to provide sufficient support; when the polyaniline content is insufficient, the conductive layer cannot fully cover the double-layer coated inorganic phase, the interfacial impedance increases, and the migration efficiency of lithium ions at the interface decreases, resulting in a decrease in ionic conductivity. In addition, insufficient polyaniline may lead to interfacial chemical instability, affecting the mechanical properties of long-term cycles.

[0183] From the test results of Example 1 and Comparative Examples 5 and 6, it can be seen that too much methoxy polyethylene glycol will introduce too many flexible segments. Although this helps to improve the ion migration ability, it will significantly reduce the mechanical strength of the composite material, resulting in a decrease in tensile strength. In addition, the excess of flexible segments may reduce the structural stability of the material and affect the cycle life; if the methoxy polyethylene glycol content is insufficient, the flexibility and amorphous region ratio of the polymer will be reduced, the lithium ion migration path will be reduced, and the ionic conductivity will be reduced. At the same time, the brittleness of the material increases, which may lead to a decrease in tensile strength.

[0184] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a sulfide-polymer composite solid electrolyte, characterized in that: The preparation method comprises: S1: The mixed powder obtained by ball milling the sulfide and the inorganic salt is heat treated in an argon atmosphere to obtain an inorganic core body; S2: melting lithium sulfide and phosphorus pentasulfide, cooling them, and then heat treating them to obtain an inorganic phase precursor; mixing the inorganic phase precursor with the inorganic core body and heat treating them to obtain a composite inorganic phase; S3: dissolving indium trichloride and lithium chloride in anhydrous ethanol, adding acetic acid and then refluxing to obtain a precursor solution, reacting the composite inorganic phase with the precursor solution, and subjecting the composite inorganic phase to a heat treatment to obtain a first coating inorganic phase; S4: dispersing ammonium fluoride and lithium acetate in anhydrous ethanol to obtain a second precursor solution, reacting the first coating inorganic phase with the second precursor solution, and subjecting the reaction to heat treatment to obtain a double-layer coating product; compounding polyaniline with the double-layer coating product to obtain a conductive layer coating inorganic phase; S5: dispersing polyetheretherketone in concentrated sulfuric acid to obtain sulfonated polyetheretherketone, and reacting the sulfonated polyetheretherketone with methoxy polyethylene glycol to obtain a modified polymer; S6: Dispersing the modified polymer in N,N-dimethylformamide, adding a conductive layer-coated inorganic phase, a cross-linking agent, an initiator and a lithium salt, and mixing to obtain a uniform mixed solution, and casting the film to obtain a composite solid electrolyte by cross-linking.

2. The method for preparing a sulfide-polymer composite solid electrolyte according to claim 1, characterized in that: In S1: The sulfide is lithium sulfide and phosphorus pentasulfide, and the molar ratio of lithium sulfide to phosphorus pentasulfide is 7-8:3; The inorganic salt is any one of lanthanum trichloride, gallium chloride, and aluminum trichloride, or a combination of at least two thereof; The molar ratio of the sulfide to the inorganic salt is 1:0.05-0.

15.

3. The method for preparing a sulfide-polymer composite solid electrolyte according to claim 1, characterized in that: In S2: The molar ratio of lithium sulfide to phosphorus pentasulfide is 2-2.5:1; The mass ratio of the inorganic phase precursor to the inorganic core body is 8-9:

1.

4. The method for preparing a sulfide-polymer composite solid electrolyte according to claim 1, characterized in that: In S3: The molar ratio of indium trichloride to lithium chloride is 1:2-3; The concentration of indium trichloride in anhydrous ethanol is 0.1-0.3M; The adding of acetic acid to adjust the pH to 4-5; The mass ratio of the composite inorganic phase to the precursor solution is 1:8-12.

5. The method for preparing a sulfide-polymer composite solid electrolyte according to claim 1, characterized in that: In S4: The concentration of ammonium fluoride dispersed in anhydrous ethanol is 0.2-0.3 mol / L; The concentration of lithium acetate dispersed in anhydrous ethanol is 0.2-0.3 mol / L; The mass ratio of the first coating inorganic phase to the second precursor solution is 1:6-10; The mass ratio of the double-layer coated inorganic phase to polyaniline is 95:5-98:

2.

6. The method for preparing a sulfide-polymer composite solid electrolyte according to claim 1, characterized in that: In S5: The mass fraction of the polyetheretherketone in concentrated sulfuric acid is 4-5wt.%; The mass ratio of the methoxy polyethylene glycol to the sulfonated polyetheretherketone is 1-2:

1.

7. The method for preparing a sulfide-polymer composite solid electrolyte according to claim 1, characterized in that: In S6: The mass fraction of the modified polymer in N,N-dimethylformamide is 10-15wt.%; The cross-linking agent is polyethylene glycol dimethacrylate, and the mass ratio of the cross-linking agent to the modified polymer is 0.2-0.3:

1.

8. The method for preparing a sulfide-polymer composite solid electrolyte according to claim 1, characterized in that: In S6: The initiator is azobisisobutyronitrile, and the amount of the initiator is 0.5-0.15% of the mass of the cross-linking agent; The lithium salt is any one of lithium perchlorate and lithium tetrafluoroborate or a combination of the two; The concentration of the lithium salt in the uniform mixed solution is 0.1-0.3M.

9. The method for preparing a sulfide-polymer composite solid electrolyte according to claim 1, characterized in that: In S6: the mass ratio of the modified polymer to the conductive layer-coated inorganic phase is (20-40): (60-80).

10. A sulfide-polymer composite solid electrolyte prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Low-interfacial-resistance sulfide solid electrolyte material for lithium batteries and preparation method

    CN110518281A

  • Sulfide solid electrolyte and high-temperature liquid-phase preparation method thereof

    CN112670560A

  • Prefabricated module of solid-state battery, solid-state battery and preparation method of solid-state battery

    CN114759266A

  • Coated solid electrolyte material as well as preparation method and application thereof

    CN115395087A

  • Solid electrolyte, secondary battery, battery module, battery pack, and electric device

    CN118367199A